Cheffes de cuisine : women and work in the professional French kitchen - Black, Rachel, 1975- (University of Illinois Press, 2021)
"Though women enter France's culinary professions at higher rates than ever, men still receive the lion's share of the major awards and Michelin stars. Rachel Black looks at the experiences of women in Lyon to examine issues of gender inequality in France's culinary industry. Known for its female-led kitchens, Lyon provides a unique setting for understanding the gender divide, as Lyonnais women have played a major role in maintaining the city's culinary heritage and its status as a center for innovation. Voices from history combine with present-day interviews and participant observation to reveal the strategies women use to navigate male-dominated workplaces or, in many cases, avoid men in kitchens altogether. Black also charts how constraints imposed by French culture minimize the impact of #MeToo and other reform-minded movements. Evocative and original, Cheffes de Cuisine celebrates the successes of women inside the professional French kitchen and reveals the obstacles women face in the culinary industry and other male-dominated professions"--